THE DOWNREGULATION OF GENES CONTROLLING VASCULAR TONE IN KIDNEYS OF ISIAH RATS WITH STRESS-INDUCED ARTERIAL HYPERTENSION - O. E. Redina; L. O. Klimov; N. I. Ershov; T. O. Abramova; L. N. Ivanova; L. A. Markel (Вавиловский журнал генетики и селекции)
The transcriptional activity of genes was studied in kidneys of hypertensive ISIAH and normotensive WAG rats in order to detect genes significantly expressed in kidneys of just one of the analyzed strains. Gene profiling was performed on the Illumina RatRef-12 Expression BeadChip microarray platform. The expression of three genes (Klk1, Klk1c10, and Kng1) related to the kallikrein-kinin system was significant in the WAG renal cortex but was not detected in hypertensive kidneys. The downregulation of these three genes and Gucy1a3 in ISIAH renal cortex suggests the weakened function of the kallikrein-kinin system in hypertensive kidneys, which may cause blood circulation disturbances in renal glomeruli and mediate the development of hypertension in ISIAH rats. The functional annotation of the genes significantly expressed in renal medulla of just one of the compared rat strains revealed the genes involved in immune response regulation.